ANALISA PROFIT MAKSIMUM USAHATANI LADA KELOMPOK TANI BERKAH MANDIRI DI DESA BATUAH, KECAMATAN LOA JANAN, KABUPATEN KUTAI KARTANEGARA - Aulia Farah Diba; Ernita Obeth; Jamaluddin (JURNAL AGRIMENT, 2020)
One of the goals of agricultural development is to increase the welfare of farmers, but in fact, there are still many farmers who are not economically prosperous. Increasing the welfare of farmers can be achieved through the success of farming. The achievement of maximum profit is one indicator of the success of the farming business. Batuah Village, which is located in Loa Janan District, is one of the largest producing areas in East Kalimantan. So far, it is not known whether the pepper farming in Batuah Village has reached its maximum profit. This is what encourages researchers to analyze the maximum profit of pepper farming in Batuah Village. The purpose of this study is to determine how much maximum profit that can be received by farmers based on the total costs that have been incurred. Data obtained through interviews with respondents using a questionnaire. The data obtained were then analyzed using multiple linear regression methods. The results showed that the maximum profit that the Berkah Mandiri farmer group could get in Batuah Village was Rp. 9,183,253 / ha achieved at a production rate of 560 kg / ha. So far, farmers have not reached the maximum production and maximum profit because the average farmer's production is 517 kg / ha and the average farmer's profit is Rp. 7,548,229 / ha. Therefore, to achieve maximum profit, pepper farmers in the Berkah Mandiri farmer groups need to increase their productivity.